2018
DOI: 10.1186/s12889-018-5388-7
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of young smokers in quitting smoking in twin cities of Pakistan: a phenomenological study

Abstract: BackgroundSmoking is highly prevalent in Pakistan claiming the lives of over 100,000 individuals every year. A significant proportion of smokers (24.7%) make an attempt to quit each year but 97.4% fail to quit successfully. Little is known about the reasons for, and experiences of, failed quit attempts. This study was carried out to explore the experiences of young male smokers in quitting smoking in the twin cities of PakistanMethodA qualitative study was carried out using a phenomenological approach in Rawal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
28
0
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 44 publications
8
28
0
12
Order By: Relevance
“…Therefore, teenagers in Aceh and the world at large are highly influenced by their associates, and hence, they tend to adopt common behaviors [41]. Furthermore, this is in agreement with other research that reported that habit was driven by peer pressure and fashion [42].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, teenagers in Aceh and the world at large are highly influenced by their associates, and hence, they tend to adopt common behaviors [41]. Furthermore, this is in agreement with other research that reported that habit was driven by peer pressure and fashion [42].…”
Section: Discussionsupporting
confidence: 89%
“…This study showed inquisitiveness to be a major factor contributing to the risk of smoking among adolescents in Aceh, supporting previous studies that reported a close relationship between seeking a sensation and cigarette use. Conversely, the search for an increased thrill was significantly associated with e-cigarette experience among Texas teens [57], driven by curiosity, peer pressure, and fashion [42].…”
Section: Discussionmentioning
confidence: 90%
“…Therefore, teenagers in Aceh and the world at large are highly influenced by their associates, and hence, they tend to adopt common behaviors [41]. This is in agreement with other research that reported that habit is driven by peer pressure and fashion [42]. Thus, having friends who promote and facilitate smoking behaviors is a significant influencing factor for smoking among adolescents.…”
Section: Discussionsupporting
confidence: 86%
“…Based on this discussion, the importance of character is known, although past research has differed on the influence of parents with a history of smoking and those currently addicted. Hence, an adolescent who has parents with a for an increased thrill was significantly associated with e-cigarette experience among Texas teens [57], driven by curiosity, peer pressure, and fashion [42].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation